Enhanced high-cycle fatigue resistance of 304 austenitic stainless steel with nanotwinned grains. (February 2021) - Cui, F.; Pan, Q.S.; Tao, N.R.; Lu, L.
Graphical abstract: Highlights: Annealed heterogeneous 304 austenitic stainless steel comprising of NT and micro-sized grains with a lower tensile strength exhibits a comparable fatigue strength at 10 7 cycles and a larger fatigue limit/strength ratio, compared to the stronger counterpart comprising of NT and dislocation structures. Such superior fatigue resistance mainly arises from a weakened strain-localized fatigue mechanism where NT grains can co-deform plastically with surrounding micro-sized grains with enhanced dislocation slipping and martensitic transformation, without cracks formed at their interface. The weakened strain-localized fatigue behavior is inherent to the heterogeneous nanotwin structure, which is fundamentally distinct from traditional strain-localizing fatigue behaviors of conventional metals with homogeneous structures. Abstract: Introducing high density of nanotwins (NT) into metals is regarded an effective strategy to achieve superior mechanical properties. Our study shows that heterogeneous structured 304 austenitic stainless steel comprising of NT and micrometer-sized grains with a lower strength exhibits a comparable fatigue strength and larger fatigue limit/strength ratio, compared to its counterpart comprising of grains with NT and dislocation structures, distinct from the traditional fatigue view. Such superior high-cycle fatigue resistance arises from a weakened strain-localized fatigue mechanism where some NT grains co-deform plastically with a large volume fraction of surrounding microsized grains with enhanced dislocation slipping and martensitic transformation.